Praktikum Berbasis Fun Chemistry untuk Meningkatkan Minat Belajar Siswa di SMA Negeri 1 Pagimana - Vivi Dia Afrianti Sangkota; Weny J.A. Musa; Erga Kurniawati; Najmah Najmah; Haris Munandar; Thayban Thayban; Auli Irfah (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
Chemistry learning at the high school level often faces challenges in how to create interesting and fun learning for students. the current paradigm of chemistry subjects is often considered scary by students, so it is necessary to take an innovative approach with the main focus of this service is to create a positive and inspiring learning experience in the school environment, motivating students to be more actively involved in chemistry learning. The service aims to explore the implementation of fun chemistry practicum as a strategy to increase students' interest in learning at SMA Negeri 1 Pagimana. This practicum was designed with the aim of changing the conventional chemistry learning paradigm into a fun and memorable experience. Through interactive and visual experiments, students are invited to actively participate in practical activities involving simple chemical reactions and demonstrations that arouse their curiosity. The initial evaluation showed a positive change in students' behavior as seen from their enthusiasm in participating in this activity.